Experimental Investigation of the Biodiesel Direct Injection and Diesel Fuel as Premixed Charge on CI-Engine Emissions, Performance, and Combustion Characteristics - Medhat Elkelawy; Hagar Alm ElDin Mohamad; Elshenawy Abd elhamid; Mahmoud El-Gamal (Journal of Engineering Research - Egypt, 2023)
This study aims to investigate the use of waste cooking oil biodiesel blend (B30D70) in CDC mode and the use of different premixing ratios of diesel vapor (15%, 20%, 25% and 30%) through manifold injection at a manifold premixed temperature of 110 ⁰C in PCCI mode when using biodiesel blend (B30D70) as the main fuel and diesel as the premixed fuel. The experiments were carried out on 4-stroke, single-cylinder, air cooled, DI diesel engine which was modified to run in PCCI mode with adding a fuel vaporizer to create the external homogeneous mixture. The engine combustion parameters, performance, and emissions characteristics were fully discussed, and the results were compared with these of CDC mode fueled by diesel. The obtained results for the use of B30D70 fuel indicates a certain decrement for exhaust gas temperature, HC, and CO emissions, but with a penalty in brake thermal efficiency, NOx, and smoke opacity. The experiments revealed that the best results were indicated for 20% diesel vapor in PCCI mode as CO, HC, NOx, and EGT reduced by 34.62%, 43.75%, 2.65% and 8.53% respectively and almost has the same BTE compared to CDC mode fueled by diesel. While increasing PR to 25% and 30% decrease the volumetric efficiency leads to rich mixture and deterioration of combustion and increase CO, HC and smoke emissions.